Montelukast: More than a Cysteinyl Leukotriene Receptor Antagonist? - Gregory R. Tintinger; Charles Feldman; Annette J. Theron; Ronald Anderson (The Scientific World Journal)
The prototype cysteinyl leukotriene receptor antagonist, montelukast, is generally considered to have a niche application in the therapy of exercise- and aspirin-induced asthma. It is also used as add-on therapy in patients whose asthma is poorly controlled with inhaled corticosteroid monotherapy, or with the combination of a long-acting β(2)-agonist and an inhaled corticosteroid. Recently, however, montelukast has been reported to possess secondary anti-inflammatory properties, apparently unrelated to conventional antagonism of cysteinyl leukotriene receptors. These novel activities enable montelukast to target eosinophils, monocytes, and, in particular, the corticosteroid-insensitive neutrophil, suggesting that this agent may have a broader spectrum of anti-inflammatory activities than originally thought. If so, montelukast is potentially useful in the chemotherapy of intermittent asthma, chronic obstructive pulmonary disease, cystic fibrosis, and viral bronchiolitis, which, to a large extent, involve airway epithelial cell/neutrophil interactions. The primary objective of this mini-review is to present evidence for the cysteinyl leukotrien–independent mechanisms of action of montelukast and their potential clinical relevance.